2023
DOI: 10.3390/ijms24109053
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Molecular Mechanisms of Autonomic Nervous System Neuron Induction through Integrative Bioinformatics Analysis

Abstract: In vitro derivation of human neurons in the autonomic nervous system (ANS) is an important technology, given its regulatory roles in maintaining homeostasis in the human body. Although several induction protocols for autonomic lineages have been reported, the regulatory machinery remains largely undefined, primarily due to the absence of a comprehensive understanding of the molecular mechanism regulating human autonomic induction in vitro. In this study, our objective was to pinpoint key regulatory components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The correlation coefficients between receptor‐transduced iPSCs and wild‐type iPSCs (WT‐iPSCs) or MOCK‐iPSCs were > 0.98, indicating a high degree of similarity between the iPSC lines. However, the correlation coefficients between differentiated NCCs derived from WT‐iPSCs (day 13 of induction [ 21 , 23 ]) as a negative control and each type of iPSC line ranged 0.69–0.7, which were lower than the values obtained for different iPSC lines. Clustering analysis revealed that NCCs and iPSC lines clustered separately.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The correlation coefficients between receptor‐transduced iPSCs and wild‐type iPSCs (WT‐iPSCs) or MOCK‐iPSCs were > 0.98, indicating a high degree of similarity between the iPSC lines. However, the correlation coefficients between differentiated NCCs derived from WT‐iPSCs (day 13 of induction [ 21 , 23 ]) as a negative control and each type of iPSC line ranged 0.69–0.7, which were lower than the values obtained for different iPSC lines. Clustering analysis revealed that NCCs and iPSC lines clustered separately.…”
Section: Resultsmentioning
confidence: 99%
“…(OS‐762RC; Optime, Tokyo, Japan). Subsequently, iPSCs were differentiated into neural crest cells (NCCs), as previously reported [ 21 , 23 ]. Briefly, NCCs were induced from Ebs using knockout serum replacement (KSR) medium and N2 medium with graded addition of nerve growth factors and signaling factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further analyze the PPIN of KIF5A using two local ranking methods degree (Pk) and maximum neighborhood component (MNC) and two global methods (bottleneck and closeness) with the help of the Cytoscape (v3.8.0) (Shannon et al, 2003) plugin CytoHubba (Chin et al, 2014). Using CytoHubba, we can identify the top 10 nodes which could play an important role in controlling the network and signal propagation (Chen et al, 2023;Takayama et al, 2023;Gu et al, 2023). We also performed the computational knockout experiments by eliminating the top significant node, resulting in network perturbations, a phenomenon known as the centrality-lethality rule (Jeong et al, 2001;Malik et al, 2019).…”
Section: Kif5a-ppin and Its Functional Modulesmentioning
confidence: 99%